2018
DOI: 10.1080/10447318.2018.1426897
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Social Interaction in Care Environments: Exploring Stakeholder Perspectives on the Potential of Interactive Technology

Abstract: This paper explores care stakeholders' perspectives on how interactive technology can help form socially active environments in residential care settings. Based on participatory workshops, involving representatives from multiple stakeholder groups, we identify a set of considerations relevant for design of social inclusion technology for care settings. The design considerations relate to the following topics: Users, Places, Themes, Value and Role. We also present three mock-ups emanating from the workshops, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This study begins to address the gaps in our knowledge about how workers mediate the deployment of new technology in RACFs. Our findings build on recent research that examined stakeholder perspectives in the design of social technology for use in care environments [5], and contributes to an ongoing conversation in HCI on best practices for designing and deploying new technology to support people as they age [14,16,21]. Future research should be conducted with larger participant groups across several RACFs, and take place over longer periods of time, incorporating co-design and codeployment opportunities, and long-term evaluations of deployment impacts across the RACFs in terms of processes, policies and the way participants perform their jobs [20].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This study begins to address the gaps in our knowledge about how workers mediate the deployment of new technology in RACFs. Our findings build on recent research that examined stakeholder perspectives in the design of social technology for use in care environments [5], and contributes to an ongoing conversation in HCI on best practices for designing and deploying new technology to support people as they age [14,16,21]. Future research should be conducted with larger participant groups across several RACFs, and take place over longer periods of time, incorporating co-design and codeployment opportunities, and long-term evaluations of deployment impacts across the RACFs in terms of processes, policies and the way participants perform their jobs [20].…”
Section: Discussionmentioning
confidence: 68%
“…For example, the use of social technology to alleviate loneliness among older adults who live independently [16,22]. There is also growing recognition that new technology has the potential to enrich the lives of older adults living in RACFs [5,10,14]. Despite this, there is limited knowledge of the role RACF workers play in mediating the deployment of new technology.…”
Section: Introductionmentioning
confidence: 99%
“…These are often group activities. Previous research has shown that staff consider group activities to be a more efficient use of their time than one-on-one activities [ 5 ]. This creates a significant barrier for the use of technologies, such as VR and videoconferencing, which typically require one-on-one facilitation by a care provider.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, where this study was conducted, this is provided through both residential care, for people living in care homes, and community-based care, for people living independently. In both types of care settings, social enrichment is often provided through a program of structured activities, which might include group games such as bingo, exercise, and music [ 5 , 6 ]. Many organizations are now incorporating technology-based activities into their social programs.…”
Section: Introductionmentioning
confidence: 99%